What is the best imaging test for patients with suspected scaphoid fractures and normal plain radiographs?. Issue 7 (July 2017) - Li, Eric; Sanford, Christopher
Abstract : EVIDENCE‐BASED ANSWER : For a patient with a suspected scaphoid fracture but normal plain radiographs, computed tomography (CT), magnetic resonance imaging (MRI), and bone scintigraphy are all reasonable next‐step imaging modalities (SOR: A, meta‐analysis of cohort studies). From a healthcare spending perspective, CT or MRI may be more cost effective than a strategy of immobilization with follow‐up after 2 weeks for repeat plain radiographs and orthopedic consultation (SOR: B, cost‐effectiveness analysis).